Out-of-Plane bending behavior of a novel double steel plate concrete Composite-New tubular roof structure - Liang Yue; Yue Yang; Yi-Ran Liang; Li-Yan Xu; Jie Xu; Chen Wang (Tunnelling and Underground Space Technology, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Pre-transport dietary chitosan improves the physiological robustness of juvenile largemouth bass (Micropterus salmoides) by modulating antioxidant and inflammatory responses - Hong-Zheng Zhao; Yu-Lin Chang; Chang Wang; Yu-Yun He; Yi-Ran Zhao; Yi-Chen Dong; Xu-Xiong Huang; Guo-Fang Zhong (Fish & Shellfish Immunology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Groundwater dynamics induced by tunneling and reservoir filling at the site of Kala hydropower project - Ao Liu; Ying-Feng Zhang; Yi-Feng Chen; Ran Hu; Zhibing Yang; Jia-Qing Zhou; Hai-Sheng Zheng; Heng-Yi Gan; Bin Chen; En-Ming Zhang (Tunnelling and Underground Space Technology, 2026)

Inhibition of Sonic Hedgehog signaling pathway by GANT61 alleviates adenomyosis by suppressing epithelial-to-mesenchymal transition, cell migration and proliferation - Zaifan Lin; Simiao Yan; Qingzhen Ran; Qianxin Yang; Haixin Lin; Jingtong Sun; Yi Chen; Xiuchi Zhong; Yingzhou Tian; Wanqun Chen (Tissue and Cell, 2026)

Macroscopic crack ratio as a structural surrogate linking linear filtration and nonlinear expression in sludge dewatering - Yi-Wen Yuan; Hao-Ran Chen; Zhi-Hao Liu; Shi-Yu Ren; Chang-Ji Huang; Raymond Jianxiong Zeng; Hou-Feng Wang (Process Safety and Environmental Protection, 2026)

A validated field-to-model framework for pesticide residue prediction and dietary risk assessment in pear production - Ran Yi; Chen Chen; Nan Huang; Xinquan Wang; Yanhua Wang; Jing Wang (Food Control, 2026)

PFDA exposure promotes myocardial aging and fibrosis via hyperactivation of the MTORC1 signaling axis - Xiao Guang Chen; Ze Yu Liao; Yi Zhang; Ran Li (Food and Chemical Toxicology, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Soy milk fermented by Bacillus subtilis SP-8-5 and Lactiplantibacillus plantarum 4_3 exhibits sedative-hypnotic ability in vivo - Zhen Liu; Zhao-Ying Zeng; Yu-Jin Li; Bin Zhou; Shi-Yi Sun; Xia Ou; Hua Qi; Chen-Jian Liu; Xiao-Ran Li (Food Research International, 2026)

Subchronic PM2.5 exposure exacerbates chronic stress-induced depression-like pathology in mice - Haoyu Lu; Xiaohui Zhao; Ran Ning; JunKoo Yi; Zhongmei He; Yan Zhao; Jianan Geng; Jia Zhou; Weijia Chen; Rui Du (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Impact of waste biomass binders on the pelletizing, combustion, and engineering feasibility of sludge–coal slime co-pelletized fuel - Hao-Ran Chen; Yi-Wen Yuan; Zhi-Hao Liu; Chang-Ji Huang; Shi-YuS Ren; Hou-Feng Wang; Raymond Jianxiong Zeng (Environmental Research, 2026)

Dual-enhancement strategy for high-performance multimodal hydrogel sensors in deep learning-assisted speech recognition systems - Xiang Di; Liqi Li; Yi Wang; Weiqiang Ran; Zihan Chen; Yaning Feng; Bo Yu; Jiawen Hou; Di Chen; Chungang Yuan (Chemical Engineering Journal, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A self-oxygenating, ROS-responsive nanoplatform potentiates sonodynamic-immunotherapy via STING activation in pancreatic cancer - Qiyi Feng; Xiao Wen; Chunxiu Xiao; Zhifan Wang; Qingqing Ran; Ling Wang; Sisi Yi; Xiuli Zheng; Zhaoyan Chen; Fangyuan Tian; Junjie Xiong; Haibo Wang; et al. (Chemical Engineering Journal, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Decoding the dynamic formation of bolus: A multimodal fusion and simulation framework for texture perception-regulated oral processing - Che Shen; Xinyu Jiang; Lizhang Wu; Zidong Chen; Zihao Li; Ran Wang; Wenxi Qi; Yi Zhang; Xinying Zhou; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

The effect of high-pressure homogenization pressure on the 3D printing of potato protein secondary emulsion - Yi Liu; Hao-ran Chen; Ao-xue Qie; Chong-hao Bi; Zhi-gang Huang; Quan-lai Li; Qiu-yue Du (Food and Bioproducts Processing, 2026)

Active intermediate water-mediated kinetic promotion for synergistic solar evaporation and photocatalytic mineralization - Xuanting Li; Jinchi Li; Xinrong Huang; Qian Chen; Xinyu Li; Hongbing Wang; Jiang Gong; Ran Niu; Yi Lu; Xiaoke Li (Chemical Engineering Journal, 2026)

LC-HRMS profiling of processing-induced formation of carcinogenic N-nitrosamines in Areca nut products - Yuan-Jhe Chang; Hsueh-Ju Lu; Yet-Ran Chen; Yi-Jhen Wang; Rajendra Bose Muthukumaran; Chiung-Wen Hu; Mu-Rong Chao (Food Chemistry, 2026)

Interplay of fracture roughness and wettability on immiscible displacement under favorable conditions: A lattice Boltzmann simulation with an improved wetting treatment - Han Huang; Yi-Feng Chen; Zhibing Yang; Ran Hu; Jia-Qing Zhou (Advances in Water Resources, 2026)

Leveraging industrial symbiosis benefits from multi-source heavy metal hazardous waste co-reutilization with industry kilns for anthropogenic metal recovery: Methods and applications - Long Wen; Luying Xiao; Yi Yao; Zhisong Ran; Yang Yue; Xiaojia Chen; Beijia Huang; Yao Wang (Journal of Cleaner Production, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Contrasting meridional displacement of the western and eastern North Pacific Subtropical Gyre occurred during ∼4.5–3.5 Ma: A response to strengthened SST gradient - Ting Chen; Yixuan Wang; Ran Wei; Yi Zhong; Qingsong Liu (Global and Planetary Change, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Does corporate climate risk promote climate response actions? Empirical evidence from China - Ran Yi; Yunfan Zhang; An Chen (Mitigation and Adaptation Strategies for Global Change, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Seaward expansion of mangrove wetlands in the Dafeng Estuary, Beibu Gulf from 1988 to 2022 - Yi Chen; Zhijun Dai; Xuefei Mei; Hu Huang; Mingquan Cai; Yangyang Xi; Ran Chen (Marine Environmental Research, 2026)

Enhanced removal of cytotoxicity from wastewater by silica gel-activated ferrate (VI) - Si-Yi Shi; Yao Lu; Yi-Ran Wan; Chang-Jie Yuan; Wei Hu; Min Liu; Ying Chen; Ye Du (Journal of Hazardous Materials, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Microbial metabolic functions, rather than taxonomic composition, predominantly shape the distribution of antibiotic resistance genes in an effluent-impacted hyporheic zone - Yina Zou; Wenlong Chen; Longfei Wang; Yi Li; Ziyi Wang; Ran Tao (Water Research, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Role of LuxS/AI-2 quorum sensing in Staphylococcus aureus biofilm formation, intestinal damage and pathogenesis in loach (Misgurnus anguillicaudatus) - Miaomiao Chen; Yuyang Duan; Wenqing Yang; Jiajia Chen; Qiujin Wang; Yuyan Xu; Xuetian Li; Xinyu Ran; Yi Li (Fish & Shellfish Immunology, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Profiling of Oryza Sativa Sulfotransferase Genes Associated with Oxyfluorfen and Fluroxypyr-Meptyl Metabolism - Li Qing Zeng; Xiao Yu Zhong; Nian Hua Teng; Xu Zhen Shi; Yi Zhuo Wang; Xi Ran Cheng; Ying Yu Zeng; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Recovery of siliceous ecosystems promoted Early Silurian climatic cooling - Huan Xu; Bo Ran; Terry T. Isson; Xinyang Chen; Chao Luo; Yi Li; Yiqing Zhu; Tong Sun; Yuyue Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Integrating justice into the assessment of urban disaster resilience construction efficiency: considering the undesirable welfare losses of vulnerable groups - Ran Yi; Yanan Chen; An Chen (Journal of Environmental Management, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Impact of tris (2-chloropropyl) phosphate and triphenyl phosphate on honeybee (Apis mellifera L.) midgut health: Assessing toxicity and potential mitigation with melatonin - Rongyi Ye; Yihan Wang; Kebo Wang; Ran Yi; Fengjiao Sun; Nan Huang; Tianliang Zhang; Yanhua Wang; Chen Chen (Journal of Hazardous Materials, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

A study on the impact of digitalization on green agricultural development and its spatial effects in China - Xiaowen Dai; Yao Li; Ying Qi; Yi Chen; Yanqiu He; Ruiping Ran; Qi Yin (Environment, Development and Sustainability, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Coping or adapting? Exploring regional priority of capacity building for disaster resilience - Yanan Chen; Ran Yi; Jiahe Li; An Chen (Journal of Cleaner Production, 2025)

Data-driven differentiable model for dynamic prediction and control in wastewater treatment - Yun-Peng Song; Wen-Zhe Wang; Yu-Qi Wang; Wan-Xin Yin; Jia-Ji Chen; Hao-Ran Xu; Hao-Yi Cheng; Fang Ma; Han-Tao Wang; Ai-Jie Wang; Hong-Cheng Wang (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Novel carbonylomics with stable isotope-coded derivatization for non-targeted analysis of reactive carbonyl species in cooking oils - Chiung-Wen Hu; Yuan-Jhe Chang; Yi-Jhen Wang; Yet-Ran Chen; Marcus S. Cooke; Mu-Rong Chao (Journal of Hazardous Materials, 2025)

Evaluating the combined toxicity of broflanilide and myclobutanil on honeybees (Apis mellifera L.): Molecular mechanisms and protective effects of curcumin - Rongyi Ye; Ran Yi; Yihan Wang; Nan Huang; Yanhua Wang; Chen Chen (Journal of Hazardous Materials, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Soil health assessment of urban forests in Nanchang, China: Establishing a minimum data set model - Fei Huang; Jiamei Tu; Foyi Zhang; Jingwang Ran; Yi Wang; Wei Liu; Wenxuan Chen; Xinyao Wang; Qiong Wang (Soil Biology and Biochemistry, 2025)

In situ transglutaminase cross-linking mediated protein-stabilized high internal phase emulsion gels to emulate dorsal adipose tissue: The role of continuous phase networks - Liang Guo; Yu-hang Xue; Yi-ran Zhang; Wen-yan Chen; Yao-siyi Yuan; Shen-shen Tian; Yue-Cheng Meng; Jie Chen (Food Chemistry, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

The interaction between banana polyphenols and starch improves the bioavailability of polyphenols after non-co-heating complexation - Yajuan Qin; Jingfeng Ran; Xiaoai Chen; Xuan Zhang; Yutong Zhang; Fei Xu; Kexue Zhu; Cuiping Yi; Yanjun Zhang (Food Hydrocolloids, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Antimicrobial p -terphenyl derivatives from the deep-sea cold seep-derived fungus Aspergillus candidus - Yi-Yi Liu; Jing-Ya Shi; Qi-Ran Liang; Guang-Ying Chen; Hai-Xin Chen; Zhuang Han; Xu-Hua Nong (Natural Product Research, 2025)

Optimizing seepage control for underground powerhouse caverns near a large-scale fault - Kai-Kun Chen; Yao-Lai Liu; Ji-Yuan Yu; Yi-Feng Chen; Ran Hu; Zhibing Yang; Jia-Qing Zhou (Tunnelling and Underground Space Technology, 2025)

Nitrate ameliorates myelin loss and cognitive impairment in Alzheimer’s disease through upregulation of neuronal sialin and subsequent inhibition of TPPP phosphorylation - Xinyue Chen; Geng Hu; Lirong Chang; Xiaoyu Li; Yi Tang; Yan Wu; Ran Zhang; Chunmei Zhang; Jinsong Wang; Xue Wang; Songlin Wang (Science Bulletin, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Paleoceanographic and paleoenvironmental changes in the high-latitude Southern Ocean during late Quaternary: progress and prospects based on the Chinese Antarctic Expeditions - Li Wu; Rujian Wang; Wenshen Xiao; Qingmiao Li; Kaitao Ni; Ran Xu; Yi Chen (Acta Oceanologica Sinica, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Bed-immersion-ratio variation as an efficient strategy to regulate denitrification efficiency directionally in elemental sulfur packed-bed reactors - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xinjie Chen; Wenyan Mao; Xiangli Zeng; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Evaluating urban climate resilience in the Yangtze River Delta urban agglomeration: A novel method integrating the DPSIR model and Sustainable Development Goals - Ran Yi; Yanan Chen; An Chen (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

On the permeability-surface area-porosity relationship for dissolving porous media - Kai Li; Ran Hu; Ya-Nan Zhang; Zhibing Yang; Yi-Feng Chen (Advances in Water Resources, 2025)

Numerical simulation of tracer breakthrough curves in karst aquifers by a coupled discrete-continuum model - Xiaokang Zheng; Zhibing Yang; Shuangqiao Zhan; Xingwu Du; Yuncai Chen; Ran Hu; Yi-Feng Chen (Journal of Hydrology, 2024)

Study on the degradation performance of coking wastewater using an in-situ enhanced Fe2+/Fe3+ cycle dual-cathode Electro-Fenton system - Chengwang Zhao; Yufang Ran; Yao Gong; Chen Hong; Yi Xing; Yunxiao Sun; Hao Wang; Wei Ling; Yijie Wang; Weibo Feng; Jiachen Hou; Xinlin Zhai; et al. (Journal of Environmental Chemical Engineering, 2024)

Cu/Fe3O4 magnetic aerogel for the capture and immobilization of iodine anion from water - Xin-Yu Zhou; Kai-Wei Chen; Ao-Tian Gu; Hui-Ran Jin; Wei-Jie Sun; Shu-Chao Song; Shan Yun; Ping Mao; Yi Yang; Jing Chen (Journal of Cleaner Production, 2024)

Dissect the association between per- and polyfluoroalkyl substances (PFAS) and kidney function from the perspective of lipid molecules - Yi-Ran Chen; Shao-Bin Lin; Jia-Yun Lv; Yan Wu; Wen-Ru Feng (Environmental Pollution, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

LiF-enriched interphase promotes Li+ desolvation and transportation enabling high-performance carbon anode under wide-range temperature - Wenbin Luo; Kuo Li; Tu Ran; Di Ma; Xingkun Chen; Haisong Wang; Yi Cheng; Xiaofei Yang (Chemical Engineering Journal, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Robust fatigue markers obtained from muscle synergy analysis - Chen Zhang; Zi-jian Zhou; Lu-yi Wang; Ling-hua Ran; Hui-min Hu; Xin Zhang; Hong-qi Xu; Ji-peng Shi (Experimental Brain Research, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

Optimization Design of Consolidation Grouting Around High-Pressure Tunnel Considering Non-Darcian Flow Effect - Yi-Feng Chen; Jin-Gang He; Wan-Jun Lei; Ran Hu; Zhibing Yang (Rock Mechanics and Rock Engineering, 2024)

Blessing or curse energy sustainability: how does climate change affect renewable energy consumption in China? - Ran Yi; An Chen (Environment, Development and Sustainability, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

New insights into microbial community for simultaneous removal of carbon and nitrogen via heterotrophic nitrification aerobic denitrification process - Weidong Xiao; Guangcai Meng; Chengzhen Meng; Ran Sun; Sihai Hu; Mengying Yi; Xue Bai; Chen Lv; Yaoguo Wu (Journal of Environmental Chemical Engineering, 2024)

The properties of Chinese Baijiu distilled spent grain-derived hydrochar: effect of in situ deep eutectic solvents formation during hydrothermal carbonization - Huan-Ran Xiong; Fan Gao; Yi Tan; Yong-Xing Chen; Zhi-Xiang Xu (Journal of Environmental Chemical Engineering, 2024)

Study on the mechanism of arsenic-induced renal injury based on SWATH proteomics technology - Xiaolu Chen; Xi Yan; Xiaoxiao Tang; Yi Wang; Xinglai Zhang; Xueshan Cao; Xiaoqian Ran; Guanwei Ma; Ting Hu; Ayesha Qureshi; Peng Luo; Liming Shen (Journal of Trace Elements in Medicine and Biology, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Variations in the concentration, inventory, source, and ecological risk of polycyclic aromatic hydrocarbons in sediments of the Lake Chaohu - Hao-Ran Tian; Xi-Tao Zhang; Li-Li Zhao; Shu-Chuan Peng; Ji-Zhong Wang; Yi-Han Chen (Marine Pollution Bulletin, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Multifunctional Eu3+-MOF for simultaneous quantification of malachite green and leuco-malachite green and efficient adsorption of malachite green - Yi-Fan Xia; Hou-Qun Yuan; Chen Qiao; Wei Li; Ran Wang; Peiyao Chen; Yan-Xia Li; Guang-Ming Bao (Journal of Hazardous Materials, 2024)

Phase diagram and permeability evolution for dissolving vertical fractures in a gravity field - Kai Li; Ran Hu; Xu-Sheng Chen; Zhibing Yang; Yi-Feng Chen (Advances in Water Resources, 2024)

Hydrochar-based facile and greenwood bio-adhesives production from distilled spent grain - Zhi-Xiang Xu; Huan-Ran Xiong; Rui Dou; Yi Tan; Yong-Xing Chen; Li-Jian Leng (Chemical Engineering Journal, 2024)

ATG5 Knockdown Attenuates Ischemia‒Reperfusion Injury by Reducing Excessive Autophagy-Induced Ferroptosis - Hua Zhu; Yi Zhong; Ran Chen; Lei Wang; Yuntao Li; Zhihong Jian; Lijuan Gu; Xiaoxing Xiong (Translational Stroke Research, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Grain-size, coarse fraction lithology and clay mineral compositions of surface sediments from Ross Sea, Antarctica: implications for their provenance and delivery mode - Li Wu; Longwei Li; Rujian Wang; Hebin Shao; Yi Chen; Zipei Lin; Yue Liu; Wenshen Xiao; Ran Xu (Frontiers in Marine Science, 2024)
Knowledge on spatial distribution, provenance and delivery mode of surface sediment aids in interpretation of nearby sediment records for paleoenvironmental reconstruction. Such knowledge, however, remains largely unknown for the modern Ross Sea, Antarctica: a key region for understanding the dynamical behavior of Antarctic Ice Sheet over geological past. In this study, we address this gap by analyzing the grain-size distribution, coarse fraction (>250 μm) lithology, and clay mineralogy of a set of surface sediment samples covering the whole Ross Sea continental shelf. Our data reveals that the sediments were mostly delivered by icebergs and bottom currents. Iceberg delivery was significantly controlled by factors such as water depth, proximity to the iceberg sources, and invasion of the Modified Circumpolar Deep Water. Bottom current activity was stronger in the Western Ross Sea (WRS) than in the Eastern Ross Sea (ERS), controlled by the formation and transport of Dense Shelf Water. Three major sorts of coarse fraction were identified, including the quartz-rich Iceberg Rafted Detritus (IRD) originating from West Antarctic glaciers and primarily distributed in the ERS, the mafic rocks-rich IRD from the Ferrar Group as well as the McMurdo Volcanic Group and mainly found in the WRS, and deformed silt traced back to the grounding zone of the David Glacier-Dragalski Ice Tongue system. The distribution of clay minerals is dominated by a distinct binary mixing pattern. Smectite and kaolinite are mainly present in the ERS, derived from beneath the West Antarctic Ice Sheet. Higher illite and chlorite contents were found offshore of the Southern Victoria Land, derived from the East Antarctic craton. Overall, these results demonstrate that the glaciers draining into Ross Sea from both the East and West Antarctic Ice Sheets are highly dynamical in the context of modern climate conditions, with implications for potential contribution to future sea level rise.

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Contrasting lake changes in Tibet revealed by recent multi-modal satellite observations - Jiangjun Ran; Lin Liu; Guoqing Zhang; C.K. Shum; Jiahui Qiu; Ruigang Hu; Jianping Li; Junhuan Peng; Cheinway Hwang; Yi Luan; Yue Sun; Min Xu; et al. (Science of The Total Environment, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

An electroconductive hydrogel with injectable and self-healing properties accelerates peripheral nerve regeneration and motor functional recovery - Zhenwei Yi; Fangke Zhan; Yijia Chen; Ran Zhang; Haodong Lin; Liming Zhao (Chemical Engineering Journal, 2023)

Abnormal activation of the Wnt3a/β-catenin signaling pathway promotes the expression of T-box transcription factor 3(TBX3) and the epithelial-mesenchymal transition pathway to mediate the occurrence of adenomyosis - Mengqi Li; Ting Li; Tingting Jin; Yi Chen; Lan Cheng; Qiheng Liang; Simiao Yan; Tingting Li; Qingzhen Ran; Wanqun Chen (Molecular Biology Reports, 2023)

Spatial distribution and migration of lead and zinc and the influence of parent materials in typical paddy soils of Hunan Province, China - Yi-fan Xiang; Da-juan Wan; Chen-ran Wang; Jun-lin Huang; Xue-ying Cao; Jia-qi Chen; Ning-xiang Ouyang (Environmental Monitoring and Assessment, 2023)

Degradation of Levofloxacin by a green zero-valent iron-loaded carbon composite activating peroxydisulfate system: Reactivity, products and mechanism - Shi-Ting Huang; Yong-Qian Lei; Peng-Ran Guo; Wen-Xuan Zhang; Jing-Yi Liang; Xie Chen; Jing-Wei Xu; Zeng-Hui Diao (Chemosphere, 2023)

Recent progress in γ-Fe2O3-based catalysts: An overview of the synthesis and applications in environmental remediation - Yuzhuo Zhou; Xin Yang; Chen Gong; Fei Zhu; Jian Wang; Yongfeng Qi; Kai Huang; Jiang Wu; Ran Chen; Yi Liu (Chemical Engineering Journal, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Exercise preconditioning promotes myocardial GLUT4 translocation and induces autophagy to alleviate exhaustive exercise-induced myocardial injury in rats - Yuan-Pan Guo; Shan-Shan Pan; Tian-Ran Chen; Yue Huang; Dong-Feng Wan; Yi-Shan Tong (Journal of Molecular Histology, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Species identification of culinary spices with two-locus DNA barcoding - Meng-Yue Zhou; Ran-Ran Xing; Ke-Han Liu; Yi-Qiang Ge; Ying Chen (Food Control, 2023)

Source apportionment of nitrate in the Pearl River Estuary using δ15N and δ18O values and isotope mixing model - Ran Long; Fei Tian; Jian-hua Chen; Yan-bo Zhou; Xue-fei Li; Yi-tong Li; Hai-wei Tang; Hai-gang Chen (Marine Pollution Bulletin, 2023)

Mass transfer during surfactant-enhanced DNAPL remediation: Pore-scale experiments and new correlation - Zejun Wang; Zhibing Yang; Ran Hu; Yi-Feng Chen (Journal of Hydrology, 2023)

Corrigendum to “Long-term environmental levels of microcystin-LR exposure induces colorectal chronic inflammation, fibrosis and barrier disruption via CSF1R/Rap1b signaling pathway” [J Hazard Mater 440 (2022) 129793] - Yue Yang; Hui Wang; Xiaoyan Wang; Ling Chen; Wenya Liu; Danping Cai; Shuxiang Deng; Hanyu Chu; Ying Liu; Xiangling Feng; Jihua Chen; Mengshi Chen; et al. (Journal of Hazardous Materials, 2023)

Effects of cryopreservation on the biomechanical properties of dentin in cryopreserved teeth: An in-vitro study - Juan Xu; Yue Chen; Min Zhou; Shouyin Yi; Juan Ran; Juanxiu Liu; Junzhou Chi; Zhu Chen; Kun Tian (Cryobiology, 2023)

Three new constituents from the Tujia ethnomedicine Swertia punicea Hemsl. - Pan Yi; Bin Li; Salman Zafar; Sajjad Ali; Wen-Bing Sheng; Yu Mao; Fang Zhou; Wen-Ming Chen; Yan-Ran Tang; Cai-Yun Peng; M. Iqbal Choudhary; Atta-ur- Rahman; et al. (Natural Product Research, 2023)

Evaluation of basin-scale hydrogeological changes induced by reservoir operation at the Xiluodu dam site - Yi-Feng Chen; Wang Ren; Zhibing Yang; Ran Hu; Yan-Pian Mao; Chuang-Bing Zhou (Journal of Hydrology, 2023)

Yellow Petal locus GaYP promotes flavonol biosynthesis and yellow coloration in petals of Asiatic cotton (Gossypium arboreum) - Yaohua Li; Lingfang Ran; Tong Mo; Nian Liu; Jianyan Zeng; Aimin Liang; Chuannan Wang; Qingwei Suo; Zhong Chen; Yi Wang; Nianjuan Fang; Shijia Xu; et al. (Theoretical and Applied Genetics, 2023)

Direct Z-scheme g-C3N4/TiO2 heterojunction porous nanotubes: An ingenious synthesis strategy to enhance photocatalytic activity - Sheng-Zhe Zhao; Ran Lu; Yi Yang; Yun Lu; Raul D. Rodriguez; Jin-Ju Chen (Journal of Environmental Chemical Engineering, 2023)

An agent-based modeling approach for public charging demand estimation and charging station location optimization at urban scale - Zhiyan Yi; Bingkun Chen; Xiaoyue Cathy Liu; Ran Wei; Jianli Chen; Zhuo Chen (Computers, Environment and Urban Systems, 2023)

Matthew effect photoimmunotheranostics enabled by proton-driven nanoconverter - Jingjing Wang; Wei Zhang; Dachong Gu; Chunmei Chen; Wei Tang; Yi Ouyang; Xiaohong Liu; Shi-Yu Lu; Wei Zhang; Xingcai Zhang; Yulong Han; Jie Hu; et al. (Chemical Engineering Journal, 2023)

Influence of inertia on liquid splitting at fracture intersections - Zexiong Zhou; Zhibing Yang; Cao Luo; Song Xue; Chi Yao; Ran Hu; Yi-Feng Chen (Journal of Hydrology, 2023)

Detection of leakage in the plunge pool area at Xiluodu arch dam with an integrated approach - Yi-Feng Chen; Sheng Wang; Wang Ren; Zhibing Yang; Ran Hu; Yan-Pian Mao (Journal of Hydrology, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Inkjet-printed MoS2-based 3D-structured electrocatalysts on Cu films for ultra-efficient hydrogen evolution reaction - Pei-Zhen Li; Na Chen; Ammar Al-Hamry; Evgeniya Sheremet; Ran Lu; Yi Yang; Olfa Kanoun; Reinhard R. Baumann; Raul D. Rodriguez; Jin-Ju Chen (Chemical Engineering Journal, 2023)

Potential health and economic impacts of shifting manufacturing from China to Indonesia or India - Qi Ran; Shao-Yi Lee; Duofan Zheng; Han Chen; Shili Yang; John C. Moore; Wenjie Dong (Science of The Total Environment, 2023)

Effects of soil and water conservation measures on sediment delivery processes in a hilly and gully watershed - Yi Zeng; Xiangdong Meng; Bing Wang; Mengjie Li; Dan Chen; Lishan Ran; Nufang Fang; Lingshan Ni; Zhihua Shi (Journal of Hydrology, 2023)

Impacts of hydraulic conditions on microplastics biofilm development, shear stresses distribution, and microbial community structures in drinking water distribution pipes - Xiao Chen; Xiao-ying Lian; Yi Wang; Sheng Chen; Yi-ran Sun; Guo-lin Tao; Qiao-wen Tan; Jing-chun Feng (Journal of Environmental Management, 2023)

Numerical modeling and data signal analysis of GPR array based on dual-field domain-decomposition time-domain finite element method - Fan Cui; Guoqi Dong; Yi Chen; Chen Wang; Deliang Teng; Ran Wang (Journal of Applied Geophysics, 2023)

Chitin oligosaccharides for the food industry: production and applications - Ran Zhang; Qiong Zhao; Zhenwei Yi; Kaihang Zhang; Jinqi Shi; Liangliang Zhu; Yijia Chen; Jiayang Jin; Liming Zhao (Systems Microbiology and Biomanufacturing, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Experimental Observation of Two Distinct Finger Regimes During Miscible Displacement in Fracture - Xu-Sheng Chen; Ran Hu; Wei Guo; Yi-Feng Chen (Transport in Porous Media, 2022)

Study on the correlation of bisphenol A exposure, pro-inflammatory gene expression, and C-reactive protein with potential cardiovascular disease symptoms in young adults - Chao-Ming Tsen; Jia-Hong Liu; Da-Peng Yang; How-Ran Chao; Jyh-Larng Chen; Wei-Chun Chou; Yi-Chen Ho; Chun-Yu Chuang (Environmental Science and Pollution Research, 2021)

Effects of Co-Applications of Biochar and Solid Digestate on Enzyme Activities and Heavy Metals Bioavailability in Cd-Polluted Greenhouse Soil - Shuaixing Xue; Fengfen Chen; Yuying Wang; Zhijiang Shao; Congguang Zhang; Ling Qiu; Yi Ran; Li He (Water, Air, & Soil Pollution, 2021)

Concatenated data and dense taxon sampling clarify phylogeny and ecological transitions within Hypotricha - Jiahui Xu; Mark Wilkinson; Miaoying Chen; Qi Zhang; Ran Yang; Zhenzhen Yi (Zoologica Scripta, 2021)
Ciliates are single‐cell eukaryotes playing important roles in various ecosystems. Phylogenetic relationships within Hypotricha, one of the most polymorphic and highly derived ciliate groups, remain uncertain. Previous studies suggested that low genetic divergence might be the reason for poorly supported SSU rDNA tree topologies, despite the high morphological diversity of this group. In this study, we substantially increase the number of available hypotrich LSU rDNA gene sequences by the addition of 857 environmental sequences, and we investigate whether a more divergent gene and dense taxon sampling could better resolve the phylogeny of Hypotricha and shed light on the patterns of ecological transitions in the evolutionary history of the group. Pairwise distances of LSU rDNA sequences are generally higher than those for SSU rDNA within each order of Hypotricha, and both concatenated rDNA and LSU rDNA trees provide more resolution for hypotrich phylogenetics. Three traditional (morphology based) hypotrich orders, Stichotrichida, Sporadotrichida and Urostylida, are polyphyletic, but a monophyletic core Urostylida are found in our trees. A brackish/marine environment is inferred as ancestral within Hypotricha, with subsequent ecological diversification into freshwater, soil environments before the origin of major clades and some transitions back to the marine. However, inferred ecological transitions in Hypotricha are influenced by genes, methods and taxa.

Aberration of Serum and Tissue N-Glycans in Mouse β1,4-GalT1 Y286L Mutant Variants - Ran Cao; Tian-Chan Zhang; Ya-Ran Chen; Cui Cao; Huan Chen; Yi-Fan Huang; Morihisa Fujita; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

A threshold stresses-based permeability variation model for microcracked porous rocks - Xing Li; Yi-Feng Chen; Kai Wei; Ran Hu; Zhi-Bing Yang (European Journal of Environmental and Civil Engineering, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Association of Corticotropin-Releasing Hormone Receptor-1 Gene Polymorphisms and Personality Traits with Violent Aggression in Male Adolescents - Li Liu; Yi Qiao; Yang Shao; Shun-ying Yu; Chen Zhang; Ran Zhang; Dong-xiang Wang; Min Zhao; Bin Xie (Journal of Molecular Neuroscience, 2020)

De Novo and Inherited SETD1A Variants in Early-onset Epilepsy - Xiuya Yu; Lin Yang; Jin Li; Wanxing Li; Dongzhi Li; Ran Wang; Kai Wu; Wenhao Chen; Yi Zhang; Zilong Qiu; Wenhao Zhou (Neuroscience Bulletin, 2019)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

Medial Preoptic Area Modulates Courtship Ultrasonic Vocalization in Adult Male Mice - Shu-Chen Gao; Yi-Chao Wei; Shao-Ran Wang; Xiao-Hong Xu (Neuroscience Bulletin, 2019)

Theoretical evaluation of group delay on pseudorange bias - Yuqi Liu; Lin Chen; Yi Yang; Hongchen Pan; Yihang Ran (GPS Solutions, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Recovery of unstable digestion of vegetable waste by adding trace elements using the bicarbonate alkalinity to total alkalinity ratio as an early warning indicator - Dong Li; Juan Sun; Qin Cao; Yichao Chen; Xiaofeng Liu; Yi Ran (Biodegradation, 2019)

The mitochondrial genome of red-necked phalarope Phalaropus lobatus (Charadriiformes: Scolopacidae) and phylogeny analysis among Scolopacidae - Wei Liu; Chaochao Hu; Wenli Xie; Peng Chen; Yi Zhang; Ran Yao; Kexin Li; Qing Chang (Genes & Genomics, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis - Pedro Leão; Yi‐Ran Chen; Fernanda Abreu; Mingling Wang; Wei‐Jia Zhang; Ke Zhou; Tian Xiao; Long‐Fei Wu; Ulysses Lins (Environmental Microbiology, 2017)
Summary Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram‐negative bacterial that live as a single individual capable of producing magnetic nano‐particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetosome and flagella biosynthesis in the magnetite magnetosome producer eMMP Candidatus Magnetananas rongchenensis. Transmission electron microscopy and focused ion beam scanning electron microscopy (FIB‐SEM) 3D reconstruction reveal that cells with a conspicuous core‐periphery polarity were organized around a central space. Magnetosomes were organized in multiple chains aligned along the periphery of each cell. In the partially sequenced genome, magnetite‐related mamAB gene and mad gene clusters were identified. Two cell morphologies were detected: irregular elliptical conical ‘frustum‐like’ (IECF) cells and H‐shaped cells. IECF cells merge to form H‐shaped cells indicating a more complex structure and possibly a distinct evolutionary position of eMMPs when compared with sMMPs considering multicellularity.

Characterization of Collagen Enzymatic Hydrolysates Derived from Lizardfish ( Synodus fuscus ) Scales - Junde Chen; Ying Liu; Ruizao Yi; Long Li; Ran Gao; Nuohua Xu; Meihua Zheng (Journal of Aquatic Food Product Technology, 2017)

Experimental Characterization and Micromechanical Modelling of Anisotropic Slates - Yi-Feng Chen; Kai Wei; Wu Liu; Shao-Hua Hu; Ran Hu; Chuang-Bing Zhou (Rock Mechanics and Rock Engineering, 2016)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Evaluation of Groundwater Leakage into a Drainage Tunnel in Jinping-I Arch Dam Foundation in Southwestern China: A Case Study - Yi-Feng Chen; Jia-Min Hong; Hua-Kang Zheng; Yi Li; Ran Hu; Chuang-Bing Zhou (Rock Mechanics and Rock Engineering, 2016)

Coupled hydro-mechanical analysis of a dam foundation with thick fluvial deposits: a case study of the Danba Hydropower Project, Southwestern China - Min Wang; Yi-Feng Chen; Ran Hu; Wu Liu; Chuang-Bing Zhou (European Journal of Environmental and Civil Engineering, 2016)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Krüppel-like Factor 8 Ameliorates Alzheimer's Disease by Activating β-Catenin - Ran Yi; Benwei Chen; Jing Zhao; Xiaorong Zhan; Liming Zhang; Xiaomin Liu; Qi Dong (Journal of Molecular Neuroscience, 2014)

Mitochondrial Dysfunction Induced by Honokiol - Jia-Xin Dong; Guang-Yuan Zhao; Qiu-Li-Yang Yu; Ran Li; Lian Yuan; Jing Chen; Yi Liu (The Journal of Membrane Biology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Toxicity of CdTe QDs with different sizes targeted to HSA investigated by two electrochemical methods - Zi-Qiang Xu; Lu Lai; Dong-Wei Li; Ran Li; Chen Xiang; Feng-Lei Jiang; Shao-Fa Sun; Yi Liu (Molecular Biology Reports, 2013)

Magnetic field can alleviate toxicological effect induced by cadmium in mungbean seedlings - Yi-ping Chen; Ran Li; Jun-Min He (Ecotoxicology, 2011)